Cocoa Pods - (:unkn) unknown (Waterman, The Hatter, Clothier and Outfitter, Trinidad, 2009)
This picture show the variety of cocoa pods, different sizes and shapes.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa trade--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Cacao--Trinidad and Tobago